GUIDELINES FOR DEVELOPING CHILD SEARCH INTERFACES - Rodolfo Bonfeti, Cristiane Lucy; Ferneda, Edberto [UNESP] (Univ Federal Campina Grande, 2019)
Studies on searching and retrieving information about children are still a topic of little prominence in the academic literature. On most sites, kids are watching and worrying about creating interfaces that use a wealth of cores and images, and a restricted access to allowed content. The way you search for information still remains similar to the adult search engine. With the development of information technologies and new pedagogical methods, how children can use a fast growing user group on the Internet. Among the many online activities, how children can use the web search feature to collect information related to their personal interests and school activities. However, informational behavior, such as cognitive and motor skills of children, is different from adults, and it is necessary to develop search engines aimed at them, in order to better assist their research tasks. The aim of this paper is to define a set of guidelines for the development of the search interface and retrieval of information used in such a diverse and heterogeneous audience as children. The methodology of this research is characterized by being bibliographic and exploratory, trying to cover articles from journals, theses, dissertations and books that address cognitive, behavioral and pedagogical aspects related to the use of technologies by children.
Keywords: Information Search; Cognition; Interfaces